2022
DOI: 10.1002/app.52183
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal aging of polyimide film

Abstract: The hydrothermal aging of a commercial polyimide film, (poly[pyromellitic dianhydride‐co‐4,4′‐oxydianiline]) is investigated, providing further insight into the well‐known loss of properties that can occur for these materials in the presence of moisture. The study involved measuring ATR‐FTIR, ultimate tensile strength, and percent elongation at break, under accelerated hydrothermal aging conditions at three different temperatures (70, 80, and 90°C). ATR‐FTIR data was analyzed using chemometrics in order to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…The sacrificial polymers behave similarly to the outer shell fabrics of firefighters' protective garments when exposed to the ageing conditions of heat, UV light, and moisture [9][10]. The exposure to ageing conditions will initiate a degradation in the sacrificial polymer layer of the sensor, ultimately disrupting the conductivity of the conductive track [8].…”
Section: Introductionmentioning
confidence: 99%
“…The sacrificial polymers behave similarly to the outer shell fabrics of firefighters' protective garments when exposed to the ageing conditions of heat, UV light, and moisture [9][10]. The exposure to ageing conditions will initiate a degradation in the sacrificial polymer layer of the sensor, ultimately disrupting the conductivity of the conductive track [8].…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that conductive tracks prepared on a meta-aramid woven fabric using reduced graphene oxide (Figure 6) resisted water immersion and the equivalent of 10 domestic launderings, while the conductivity was progressively lost as a result of abrasion [170]. Potential sacrificial polymers were successfully identified for thermal [171] and moisture [172] end-of-life sensors.…”
Section: Aging Of High-performance Polymer Fibersmentioning
confidence: 99%
“…An innovative field for metalized fibers is products like wearable E-textiles [167]. Another important application is antimicrobial textiles, mainly based on silver-coated fibers [168][169][170][171][172]. However, copper containing textile materials is also offered for antimicrobial purposes [173,174].…”
Section: Metalized Textilesmentioning
confidence: 99%
“…[20][21][22] In addition, physical aging can cause changes to the characteristic relaxation time of the polymer. 15,23 Unlike the irreversible processes of chemical 24,25 and hydrothermal aging, 26,27 physical aging can be reversed through thermal rejuvenation mechanisms like super-T g reheating. 28,29 During thermal rejuvenation, the polymer chains are brought to an equilibrium state with their surrounding by raising their temperature above T g and any previous effects of aging and mechanical loading are erased.…”
Section: Introductionmentioning
confidence: 99%